Effect of CYP4F2 Polymorphisms on Ticagrelor Pharmacokinetics in Healthy Chinese Volunteers - Nie, Shanshan; Chen, Kaifeng; Guo, Chengxian; Pei, Qi; Zou, Chan; Yao, Liangyuan; Yuan, Hongbo; Zhao, Xia; Xie, Ran; He, Xu; Huang, Jie; Yang, Guoping (Frontiers in Pharmacology, 2022)
Background: Ticagrelor is a new class of P2Y12 receptor inhibitors, which has been widely used for antiplatelet therapy. This study aimed to explore the effect of single nucleotide polymorphisms (SNPs) in metabolic enzymes, transporters, and other relevant variants on the pharmacokinetics (PK) of ticagrelor and its active metabolite AR-C124910XX. Methods: The study population comprised 68 healthy Chinese volunteers, who were enrolled in ticagrelor bioequivalence clinical trial. The PK profile of ticagrelor was evaluated after orally administering a single 90 mg dose of ticagrelor in tablet form. Plasma concentrations of ticagrelor and AR-C124910XX were determined through liquid chromatography–tandem mass spectrometry. Plasma DNA samples were used to explore the effect of gene polymorphisms on the PK of ticagrelor and AR-C124910XX with whole exome sequencing. Results: Female participants had a higher maximum plasma concentration–weight ratio (Cmax/W; P<0.001) and shorter half-life (T1/2; P<0.05) for ticagrelor than their male counterparts. In addition, a higher area under the curve–weight ratio (AUC/W; P<0.001), longer T1/2 (P<0.001) and time to reach the maximum plasma concentration (Tmax; P<0.001) as well as lower apparent drug clearance (CL/F; P<0.001) was observed among healthy volunteers in the fed trial than those enrolled in the fasting trial. For AR-C124910XX, a higher Cmax/W (P<0.001) and AUC/W (P<0.001) but a lower CL/F (P<0.001) and apparent volume of distribution (Vd/F; P<0.001) were observed among female participants. Healthy volunteers enrolled in the fasting trial exhibited higher Cmax/W (P<0.001) and AUC/W (P<0.01), shorter Tmax (P<0.001), and lower CL/F (P<0.001) and Vd/F (P<0.001) than those enrolled in the fed trial. Upon confirmation through multivariate analysis, the CYP4F2 rs2074900 AA carriers were associated with higher Cmax/W and AUC/W and lower CL/F and Vd/F than CYP4F2 rs2074900 AG and GG carriers. Conclusion: This study is the first to show that the CYP4F2 rs2074900 SNP had a remarkable effect on ticagrelor PK, which is significant since it adds to the limited pharmacogenetic information on ticagrelor.